The prevalence of manifest and latent celiac disease in type 1 diabetes mellitus - Serkan GÜVENÇ; Sabahattin KAYMAKOĞLU; Nuray GÜREL; Kubilay KARŞIDAĞ; Kadir DEMİR and Dinç DİNÇER and Çiğdem KEKİK and Serpil SALMAN and Temel YILMAZ and Fatih BEŞIŞIK and et al. (Turkish Journal of Gastroenterology, 2019)
-